Current practices and challenges in assisted reproductive technology care pathways in France and Belgium: the AMPLITUDE survey - Wyns, Christine; Blockeel, Christophe; Guivarc’h-Lévêque, Anne; Porcu-Buisson, Géraldine; Swierkowski-Blanchard, Nelly; Yazbeck, Chadi; Rongières, Catherine (Frontiers in Reproductive Health, 2025)
IntroductionThis study aimed to evaluate current practices in assisted reproductive technology (ART) patient care, identifying potential areas for improvement. Collective data will further provide key insights in gaps and potential new tools to enhance ART care practices for patients and healthcare professionals.MethodsAn online questionnaire comprising 22 multiple choice questions was distributed to ART specialists in France and Belgium between September and November 2023. Responses were analyzed overall and by country. Descriptive analysis used 5-point Likert scales (converted to numerical scores) for comparative insights. Qualitative data were reported as frequencies (%), and quantitative data as means and standard deviations.ResultsA total of 166 IVF specialists participated in the survey out of 487 contacted, 130 from France (78.3%) and 36 from Belgium (21.7%). Most respondents (92.8%) scheduled the first consultation within three months, with all Belgian specialists meeting this timespan compared to 90.8% in France. Notably, 30.8% of French specialists and 29.5% of Belgian specialists scheduled appointments within one month. During initial consultations, 73.3% provided patients with informational materials, and 61.5% informed them about psychological support options. To assess lifestyle factors, clinicians primarily used oral questionnaires (91.9%), with a higher prevalence of written questionnaires in Belgium compared to France (37.1% vs. 15.9%). When patients struggled to understand treatment instructions, 82.6% of clinicians took time to re-explain, and 60.9% referred patients to nursing staff for further assistance. Most respondents (90.7%) provided digital tools for injection training, while 74.7% offered training sessions conducted by paramedical staff. Most reported treatment errors included dosage and handling mistakes and nurse injection errors. Psychological support was offered by 80% of respondents for IVF failures, with variations between countries in follow-up approaches. Overall, clinicians rated patients’ knowledge of different ART aspects as relatively low, with average scores ranging from 2.43/5 to 3.30/5, depending on the items.DiscussionThe main areas for improvement highlighted in this study were patient education and support throughout the care pathway. Differences in practices between France and Belgium were also observed, highlighting the importance of context-adapted approaches. Our observations may further facilitate the development of tailored tools aimed at improving ART care practice.